The last battle - Lewis, C. S. 1898-1963 (Lewis, C. S. (Clive Staples), 1898-1963. Chronicles of Narnia (HarperCollins (Firm)) ;, 1994)
When evil comes to Narnia, Jill and Eustace help fight the great last battle and Aslan leads his people to a glorious new paradise.